The Influence of Transparency, Internal Control Systems, Human Resource Competency, and Community Participation on The Accountability of Village Fund Management - Br Bancin, Dela Syakillah Nuraisah; Samri Juliati Nasution, Yenni; Ahmadi Bi Rahmani, Nur (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The increasing allocation of the village fund budget each year, necessitates the Minta Kasih Village government to be responsible for the village funds managed. The Minta Kasih Village Government needs to increase community participation, internal control systems, human resource competence, and transparency in order to achieve village fund management with good accountability. The research was carried out with the aim of assessing the influence on accountability in managing village funds, individually or simultaneously, on community participation, transparency, internal control systems, competence, and increased human resources. Saturated samples were used as the research method. Multiple linear regression was used as data analysis with the help of SPSS 25 software. The research provided individual results, accountability in village fund management was influenced by community participation, internal control systems, human resource competence, and transparency positively and significantly. However, accountability in village fund management has a positive but not significant influence from community participation. Simultaneously, 78% of the significant influence given to the accountability of village fund management was on the variables of transparency, community participation and internal control system, while the influence due to other variables which were not included for research was 22%.